Analysis of expansions of a bus transit network considering the needs identified by the community: case study - Saha,Promothes (2015)
Abstract Expansion analyses are performed on a bus transit network in the City of Laramie area in Wyoming. Expansion analysis is based on the needs identified by the bus transportation agency and the community. This paper examines the expansions, operations and sustainability of a bus transit in a small city having a population of 30,000 people. When funding is limited, it is very important to identify the best route that provides the services to the more people. Gravity model and ArcGIS software have been used to analyze the data. This paper examines the background of the transportation agency and existing services, finally develops a bus routing model for identifying future expansions. This research identified that one of the existing bus stops account for 1% of the ridership which can be closed. This research also found that adding a new loop considering same number of buses would increase the ridership significantly without increasing headway.